Study on the impact of climate changes on alive's organisms - Ancuța Marin (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
The paper aims to briefly present the main problems regarding the impact of climate change on living organisms (humans, animals, plants), the measures taken so far to solve these problems and the actions that must be taken into account by the European Union and the states members. They propose increasing the resilience of health and social systems and emphasize the need to ensure adequate surveillance and control of climate change impacts on health, such as epidemiological surveillance, control of communicable diseases and the effects of extreme events. In general, climate change does not cause many new or unknown health risks, but it will intensify certain interactions between the environment and human health, with more drastic effects than at present. Most public health measures and systems already exist, but they need to be adapted to the new situation and new needs.
Keywords: Q30; Q39; Q54; 330; climate change; living organisms; health